Welcome to envy park - Esguerra, Mina V. (Mandaluyong City Anvil Publishing, Inc., 2015)
"Moira Vasquez is a doer. A planner. A get-up-and-goer. At twenty-two, she left her hometown to work in Singapore, to satisfy a need to travel as well as to give her savings account a boost. Five years later and she's back in Manila, with a shiny new apartment to her name, but no job, no career, no boyfriend. She meets Ethan Lorenzo, the quiet hunk of an IT consultant on the ninth floor of her condo building, and he's a welcome distraction during this period of having absolutely nothing going on in her life. But she has a plan-of course she does-and this is just a short layover on the way to the next country, the next job, the next big thing. Or will she be missing out on something great that's already there." -- cover.
Keywords: Philippine fiction (English).